Peningkatan Kemampuan Menulis Teks Laporan Hasil Observasi (LHO) Menggunakan Metode Cooperative Learning Kelas X TITL 1 SMKN 5 Surabaya 2024/2025 - Jumayyeh Jumayyeh; Kaswadi Kaswadi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research is a Classroom Action Research (PTK) which is an action to improve the learning system involving researchers, observers, and the subjects under study. The main purpose of this study is to improve the ability to write observation report text (lho) using the cooperative learning method for class X TITL 1 SMKN 5 Surabaya 2024/2025. Data collection was done by observation, test, interview. The results showed an increase in the percentage of students who reached the KKM score from the initial condition of 20% to 51.42% in cycle I, and increased again to 85.71% in cycle II. The application of this method also succeeded in increasing students' motivation and enthusiasm in the learning process, especially when differentiation was carried out according to each student's learning style in cycle II.